FOLIAR FERTILIZATION WITH COMMERCIAL LIQUID FERTILIZER FOR IMPROVING GROWTH AND QUALITY OF SEASHORE PASPALUM TURF - Atef Tawila; Tarek Noor El-Deen; Boshra El-Sayed; Sayed Shahin (Scientific Journal of Flowers and Ornamental Plants, 2015)
An investigation was conducted under the open field condition at the Experimental Farm of Hort. Res. Inst., ARC, Giza, Egypt during 2013 and 2014 seasons to study the effect of some commercial liquid fertilizers; super blue-green (SBG) at the rates of 1 and 3 ml/l, Kalsin-A (K-A) at the rate of 1 ml/l and the combinations between the two levels of SBG and that of K-A on growth, density and chemical composition of seashore paspalum (Paspalum vaginatum Swartz) planted in 40-cm-diameter plastic pots filled with about 6 kg of sand and clay mixture (1:1, by volume) when applied as a foliar spray, 5 times with one month interval. The control plants were sprayed with tap water only. The obtained results indicated that all single and combined treatments used in the study markedly improved all vegetative growth traits of the fertilized plants with various significant differences compared to control plants in the two seasons. Among the sole treatments, SBG at 3 ml/l treatment was the superior, whereas the same fertilizer and K-A one at 1 ml/l for each were the inferior. On the other hand, combined treatments induced a more improvement in all vegetative growth parameters than the individual ones, but the prevalence in both seasons was for SBG at 3 ml/l + K-A at 1 ml/l combined one, which gave the highest records at all. A similar trend was also observed as well regarding the leaf content of chlorophyll a, b, carotenoids, N, P, K, Ca and total soluble sugars except for 1 ml/l KA treatment which gave the highest content of Ca among the sole treatments, and the increment in total soluble sugars content was attained by the individual fertilization treatments as was not significant relative to control in both seasons. In addition, the total indole content was significantly increased in response to the different treatments used in this study to reach the maximum by the two combined treatments. The opposite was the right concerning the content of total phenols. Accordingly, it can be advised to spray the herb of seashore paspalum turf with a combination of super blue-green liquid fertilizer at 3 m/l plus Kalsin-A at 1 ml/l, five times with one month interval to obtain the best growth, coverage and colour.